Evaluation of â€œInstantiationâ€ for Cultural Heritage Information System - Razali, Suriyati; Adilah Wan Adnan, Wan (International Journal of Engineering and Technology, 2018)
This paper presents the evaluation of â€œInstantiationâ€ for cultural heritage information system. Within social-technical concerned, the soft design science was used as an approach to create â€œInstantiationâ€ as IT artifacts. The evaluation of â€œInstantiationâ€ was performed based on the â€œfunctionalities characteristicâ€ evaluation criteria. Explanation on how the verification study was conducted to evaluate constructed instantiation according to five sub-characteristics of â€œfunctionalityâ€ named as accuracy, suitability, interoperability, security, and functionality compliance is also presented. Finally, this paper concludes the results of applying information quality by highlighting the feedback that shows the â€œInstantiationâ€ created has been accepted among the museum and cultural heritage community.Â Â Â